Perceptions of self‐defined memory problems vary in south Asian minority older people who consult a GP and those who do not: a mixed‐method pilot study. (28th July 2015) - Giebel, Clarissa; Challis, David; Worden, Angela; Jolley, David; Bhui, Kamaldeep Singh; Lambat, Ahmed; Purandare, Nitin
Abstract : Objective: South Asian older adults access services for mental health problems and dementia less than other older people in the UK, unlike for physical health problems. This pilot study investigated how South Asians with self‐defined memory problems, with and without GP consultation, construe the symptoms, causes, consequences and treatment of the condition. Methods: Participants were recruited through community centres, their networks and memory clinics in Greater Manchester. The newly developed Barts Explanatory Model Inventory for Dementia (BEMI‐D) was administered to 33 (18 M, 15 F) older South Asians aged 65 or above with memory problems in English, Gujarati or Urdu. Furthermore, cognition, executive function and depression were assessed. Results: Perceptions of dementia varied by GP consultation for memory problems. A greater proportion of older adults without a consultation considered memory problems to be given by God, saw acceptance of fate as an alternative treatment and did not identify medical support as appropriate. Forgetfulness and loss of social meaning were identified as symptoms of dementia more by those with a consultation. Higher levels of diabetes, heart disease and depression were found in those without a consultation. Conclusions: Differences in perceptions may influence the decision about consulting a GP. Similarly, consultation for memory problems appears linked to extent physical health problems and mental health consultation (depression). These variations reported on a small scale in this pilot study suggest the need to explore the impact of perceptions on rates of GP consultation, so as to improve timely diagnosis and access to appropriate services. Copyright © 2015 John Wiley & Sons, Ltd.